Effect of phosphorus on growth and yield of sesame (Research in Agriculture Livestock and Fisheries, 2019)
The present study was conducted at the Research farm of Sher-e-Bangla Agricultural University, Sher-e-Bangla Nagar, Dhaka, during March to June 2014 to examine the effect of Phosphorus on the growth and yield of Sesame. BARI Til-3 variety was used for the study. This experiment was consisted of single factor eg. phosphorus. There were three levels of phosphorus viz. (i) P0 (0 % P), (ii) P1 (20 % P) and (iii) P2 (30 % P) and the experiment was laid out in a Randomized Complete Block Design (RCBD) with six replications. Different levels of phosphorus showed significant effect on growth and yield of sesame. Individually phosphorus had significant effect on highest plant height, number of leaves plant-1, number of primary branches plant-1, number of secondary branches plant-1, number of capsule plant-1, number of seeds capsule-1, 1000 seed weight, seed yield and harvest index. The highest plant height of sesame (136.30 cm), the highest no leaves plant-1 of sesame (34.44), number of primary branches plant-1 (5.56), number of secondary branches plant-1 (7.61), number of capsule plant-1 (25.87), number of seed capsule-1 (70.47),1000 seed weight (3.54), Seed yield (1581.00 kg ha-1), Stover yield (3034.42 kg ha-1), biological yield (4615.76), harvest index (34.11%), oil content (43.92%) was recorded from P1. Again, the highest days to first flowering of sesame (31.67) was recorded from P1 (20 % P) but the highest days to maturity was (85.67) recorded from P2 (30% P). Application of P at different percentage is causing effect in growth and yield of sesame.Res. Agric., Livest. Fish.6(2): 245-251, August 2019